Establishing Teachers’ Personality Competence through the Principal’s Leadership Role in Vocational High School - Nellitawati (International Journal of Psychosocial Rehabilitation, 2020)
There is a high level of substandard quality of education in Indonesia. Also, the competency tests conducted on various vocational school teachers also show unsatisfactory results, thus necessitating an investigation. This study, therefore, aims to determine the role of principals in improving a teachers’ personality competence in Vocational High Schools in Padang, Indonesia. This was conducted quantitatively and qualitatively, through the use of questionnaires and interviews, respectively. The results indicate the significant effect of the principals’ role as an educator, administrator, supervisor, leader, innovator and motivator. Also, the personality competence of 50% and within a high category explains the the positive impact in terms of character, discipline, and morale. Hence, it is possible to adopt the approach of principal assistance as guide countrywide.